Assessment of the Changing Pattern in Maize Cultivation in Sokoto-Rima River Basin, Nigeria - J O Adejuwon (Journal of Applied Sciences and Environmental Management, 2018)
Maize, a monocotyledonous crop, grown for grain and forage, is the most important cereal crop in sub-Saharan Africa. This study assessed the changing pattern in maize cultivation in Sokoto-Rima River Basin, Nigeria. Questionnaire was administered to 450 respondents from 15 agricultural settlements in 15 local governments in the study area, using clustered sampling technique. Data was analyzed using frequency counts, percentage and pairwise ttest. Results showed that 20 maize varieties exist in the basin. Ten of the twelve varieties planted in 1970's are still being cultivated, two varieties no longer exist while 8 varieties were newly introduced at the time of this investigation. Yellow maize known as ‘Ja Masara’ (40.19%) was the most popular variety in the 1970's. This was closely followed by white maize called ‘Fari Masara’ (39.57%). These two varieties still accounted for over 70% in 2000’s, with white maize accounting for 46.76%. The cultivation of yellow maize decreased by 13.43% while white maize increased by 7.19%. Yellow maize known as project variety ‘Yar Project’ (8.73%) is a new variety that is gaining popularity among the farmers. The pairwise t-test result showed no significant difference between the past and present varieties planted. The factors that determine choice of the varieties cultivated include resistance to pests and diseases, personal preference, yield, the period of maturity and resistance to drought. The cultivation maize in the Basin haves increased by 7.19% over time from 71.7% to 78.89%.